Creation of a spiritual and temporal space. Transfer of material culture and knowledge to Guaraní-Jesuit reductions (Quinto Sol, 2023)
This article deals with the transfer of material culture made by the Jesuits from Europe to the province of Paraguay during the seventeenth and eighteenth centuries, and its impact on social, economic and religious life on the indigenous people of the Guarani-Jesuit reductions, and the creation of new knowledge, composed of indigenous wisdom with European technologies in the workshops of the manual craft introduced in these reductions. This study is based on the results of a research project on the materiality of the polychrome wooden sculptures of these reductions and on the analysis of documents from different archives in Latin America and Europe.
Keywords: material culture; transfer; Jesuits; manual labor